Non-linear Lamb Waves for Locating Defects in Single-Lap Joints - Nicassio, Francesco; Carrino, Stefano; Scarselli, Gennaro (Frontiers in Built Environment, 2020)
A novel method based on Non-linear Lamb waves behavior and Local Defect Resonance (LDR) is proposed for locating and evaluating disbonds in Single-Lap Joints (SLJ) typically used in aerospace industry. The presence of damages/defects such as disbonds leads to the presence of sub- and super-harmonics components in the frequency response. The maximum acoustic wave-damage interaction is reached by particular excitation frequencies that enhance the Non-linear response causing LDR. The LDR frequency is experimentally evaluated through the appearance of a single subharmonic component in the frequency spectrum of signals received by piezoelectric transducer (PZT) bonded on the structure. The Non-linear properties of Lamb waves are exploited to make defects generate subharmonic waves at LDR frequency. An algorithm is implemented for damage/defect localization that is accurately obtained by knowing PZTs positions, Time of Flight (ToF) and propagation properties of subharmonics packet. Several disbonds with different dimensions are artificially reproduced on an aluminum SLJ: experimental and FE results show good accordance both in usual (single damage) and critical (multi-damage) scenario. The paper proposes a baseline-free method for the disbonds detection, characterization and localization in SLJs that uses the PZT signals without affecting adhesive interface, thus allowing for an active health monitoring.